Anxiety at the first radiotherapy session for non-metastatic breast cancer: Key communication and communication-related predictors. Issue 1 (January 2015) - Lewis, Florence; Merckaert, Isabelle; Liénard, Aurore; Libert, Yves; Etienne, Anne-Marie; Reynaert, Christine; Slachmuylder, Jean-Louis; Scalliet, Pierre; Van Houtte, Paul; Coucke, Philippe; Salamon, Emile; Razavi, Darius
Abstract: Background and purpose: Patients may experience clinically relevant anxiety at their first radiotherapy (RT) sessions. To date, studies have not investigated during/around the RT simulation the key communication and communication-related predictors of this clinically relevant anxiety. Material and methods: Breast cancer patients ( n = 227) completed visual analog scale (VAS) assessments of anxiety before and after their first RT sessions. Clinically relevant anxiety was defined as having pre- and post-first RT session VAS scores ⩾4 cm. Communication during RT simulation was assessed with content analysis software (LaComm), and communication-related variables around the RT simulation were assessed with questionnaires. Results: Clinically relevant anxiety at the first RT session was predicted by lower self-efficacy to communicate with the RT team (OR = 0.65; p = 0.020), the perception of lower support received from the RT team (OR = 0.70; p = 0.020), lower knowledge of RT-associated side effects (OR = 0.95; p = 0.057), and higher use of emotion-focused coping (OR = 1.09; p = 0.013). Conclusions: This study provides RT team members with information about potential communication strategies, which may be used to reduce patient anxiety at the first RT session.